2022
DOI: 10.3390/gels8100645
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Morphological, and Functional Characterization of Edible Anthocyanin-Enriched Aloevera Coatings on Fresh Figs (Ficus carica L.)

Abstract: In the present investigation, aloe vera gel (AVG)-based edible coatings enriched with anthocyanin were prepared. We investigated the effect of different formulations of aloe-vera-based edible coatings, such as neat AVG (T1), AVG with glycerol (T2), aloe vera with 0.2% anthocyanin + glycerol (T3), and AVG with 0.5% anthocyanin + glycerol (T4), on the postharvest quality of fig (Ficus carica L.) fruits under refrigerated conditions (4 °C) for up to 12 days of storage with 2-day examination intervals. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…After 16 days of storage, TSS was highest in CON (21.3 o Brix) and lowest in ChCSA (14.3 o Brix). Chitosan- and alginate-based coatings were observed to inhibit metabolic and hydrolytic reactions associated with TSS increase in various fruits, including Chinese winter jujube, longan, and fig fruits [ 27 , 40 , 41 , 42 ].Thus, low TSS in ChCSA-coated samples could be attributed to the effective combination of Ch and SA, which reduced metabolic reactions and retarded polysaccharides breakdown processes [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…After 16 days of storage, TSS was highest in CON (21.3 o Brix) and lowest in ChCSA (14.3 o Brix). Chitosan- and alginate-based coatings were observed to inhibit metabolic and hydrolytic reactions associated with TSS increase in various fruits, including Chinese winter jujube, longan, and fig fruits [ 27 , 40 , 41 , 42 ].Thus, low TSS in ChCSA-coated samples could be attributed to the effective combination of Ch and SA, which reduced metabolic reactions and retarded polysaccharides breakdown processes [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Al Hilifi et al [ 9 ] developed aloe vera gel (AVG)-based edible coatings enriched with anthocyanin and investigated the effect of different formulations of these aloe-vera-based edible coatings, such as neat AVG (T1), AVG with glycerol (T2), aloe vera with 0.2% anthocyanin + glycerol (T3), and AVG with 0.5% anthocyanin + glycerol (T4), on the postharvest quality of fig (Ficus carica L.) fruits under refrigerated conditions (4 °C) for up to 12 days of storage with 2-day examination intervals. The results of the present study revealed that the T4 treatment was the most effective for reducing the weight loss in the fig fruits throughout the storage period (~4%), followed by T3, T2, and T1.…”
Section: Contributionsmentioning
confidence: 99%
“…Abdalla et al added Sicilian lemon essential oil with antimicrobial properties to films and coatings from pectin and chitosan for strawberry preservation packaging . Al-Hilifi et al added natural antioxidant anthocyanins to aloe vera gel coating for freshness packaging of fig fruits . Zhou et al modified chitosan using glycidyl trimethylammonium, which has antimicrobial properties, and dihydroxy benzaldehyde, a natural polyphenol antioxidant, to prepare quaternate catechol-functionalized chitosan that can be used as a coating material for fruits .…”
Section: Introductionmentioning
confidence: 99%
“… 11 Al-Hilifi et al added natural antioxidant anthocyanins to aloe vera gel coating for freshness packaging of fig fruits. 12 Zhou et al modified chitosan using glycidyl trimethylammonium, which has antimicrobial properties, and dihydroxy benzaldehyde, a natural polyphenol antioxidant, to prepare quaternate catechol-functionalized chitosan that can be used as a coating material for fruits. 13 Plant essential oils are natural antibacterial and antioxidant substances.…”
Section: Introductionmentioning
confidence: 99%